Factors affecting the development of night-time economy in Mekong Delta provinces - Phan, Thi Hang Nga; Nguyen, Thi Canh (Journal of Finance - Marketing Research, 2023)
The primary objective of this study is to investigate and evaluate the various elements that contribute to the growth and evolution of the nighttime economy in the provinces located within the Mekong Delta region. The components that have been discovered encompass institutional and environmental factors, infrastructure and safety, nature and resources, labor force scale and quality, and socio-cultural characteristics. The data was obtained by administering 457 survey questions to individuals residing in the surrounding area, including managers, business owners, and tourists. Subsequently, the gathered data underwent analysis utilizing the Exploratory Factor Analysis (EFA) and Regression Analysis (RA) models. The findings of the study demonstrate that the five criteria described above have a substantial influence on the growth and progression of the nighttime economy in the provinces of the Mekong Delta. The authors suggest policy proposals to promote the growth of the nighttime economy in the provinces of the Mekong Delta, with a specific focus on the period following the Covid-19 pandemic.